Upper urinary tract urothelial carcinoma - Grasso III, Michael; Bagley, Demetrius H. (Springer International Publishing : Imprint: Springer, 2015)
This comprehensive text examines the diagnostic and treatment strategies of bladder urothelial carcinoma. The authors present a balanced scientific and practical approach to various treatments, such as diagnostic modalities,  endoscopic treatments, surgical treatments and adjuvant therapies.   Upper Urinary Tract Urothelial Carcinoma is a useful source of treatment guidelines with a strong frame of reference for designing innovative therapies and multimodal treatment plans. Many medical subspecialists such as urologists, radiologists, oncologists, pathologists and internists, who encounter complex patients, will find this book of great interest. .